Full Bio‐Based Soy Protein Isolate Film Enhanced by Chicken Feather Keratin. Issue 5 (10th March 2021) - Li, Xiaona; Wei, Yanqiang; Jiang, Shuaicheng; Zhou, Ying; Li, Jiongjiong; Li, Kuang; Shi, Sheldon Q.; Li, Jianzhang
Abstract: Soy protein isolate (SPI) film is considered a promising biomaterial for the replacement of petroleum‐based food packaging plastics. However, current SPI films are still replying on petroleum‐based crosslink agents. In this paper, a green and effective approach is developed to prepare a full biomass‐based sustainable film with high strength and toughness by incorporating feather keratin (FK, extracted from the waste chicken feathers) into the SPI via the reaction of disulfide bonds. The broken disulfide bonds in FK are recombined with the sulfhydryl group on the SPI molecular chains to form a cross‐linked network. Compared to the SPI film, the tensile strength of the SPI/FK composite film is increased by 242% to 8.2 MPa and the toughness is increased by 152% to 9.18 MJ m −3 . The thermal stability and the water resistance of the SPI/FK composite films are also improved. The replacement rate of FK‐modified SPI is up to 40%. Since the film is 100% made from bio‐based materials, it would be biodegradable. This research provides a green and economic approach to improve the performance of protein‐based food packaging films by introducing FK as an enhancer and constructing disulfide bonds cross‐linked network structure in the protein system. Abstract : Incorporating feather keratin (FK, extracted from the waste chicken feathers) into the soy protein isolate (SPI) via the reaction of disulfide bonds is a green approach to prepare a full biomass‐based film. The broken disulfide bonds in FK recombine with the sulfhydryl group on the SPI molecular chains, which forms a cross‐linked network and improves the mechanical strength of the resultant film.